1997
DOI: 10.1144/gsl.sp.1997.125.01.21
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur distribution in a multi-bed seam

Abstract: The Parkgate Seam (Langsettian) is an important seam for the coal industry in the UK. It extends over a considerable part of the East Pennine Coalfield and a large database of information on the seam has been complied by (the former) British Coal for the Nottinghamshire area from many sampling locations. The seam has been subdivided into a series of mappable units termed plies. This paper demonstrates how sulphur concentrations may vary considerably on a vertical scale and that spatial distributions within ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…High Se in Fife‐Stirling, Ayrshire, Cumberland, Northumberland, North Wales, and Staffordshire coincide with high S and visible pyrite in sampled coals. Pyrite occurs in coal as early (syngenetic) replacement minerals, and later (epigenetic) cleat‐filling pyrite (Cavender & Spears, , ; Spears & Caswell, ; Spears & Tewalt, ). Samples from the South Wales, Ayrshire and Northumberland coalfields show the highest pyrite abundance, with disseminated pyrite, banded pyrite and later stage cleat pyrite evident.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High Se in Fife‐Stirling, Ayrshire, Cumberland, Northumberland, North Wales, and Staffordshire coincide with high S and visible pyrite in sampled coals. Pyrite occurs in coal as early (syngenetic) replacement minerals, and later (epigenetic) cleat‐filling pyrite (Cavender & Spears, , ; Spears & Caswell, ; Spears & Tewalt, ). Samples from the South Wales, Ayrshire and Northumberland coalfields show the highest pyrite abundance, with disseminated pyrite, banded pyrite and later stage cleat pyrite evident.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a positive correlation in the Te/Se ratio (Figure 2), suggesting a close relationship between the two elements, both substituting for S in pyrite. Selenium can substitute readily for S in many sulphide minerals and can also be precipitated by sulphate-reducing microbes (Hockin & Gadd, 2003;Parnell, Bellis, Feldmann, & Bata, 2015 (Cavender & Spears, 1995, 1997Spears & Caswell, 1986;Spears & Tewalt, 2009 shown to be more abundant in early forms of pyrite (Large et al, 2014). However, late stage epigenetic fluids are also known to be responsible for high concentrations of trace elements in some coals (Bullock et al, 2018;Diehl et al, 2004;Spears & Tewalt, 2009;Yudovich & Ketris, 2006).…”
Section: Source and Enrichment Of Se And Te In British Coalsmentioning
confidence: 99%
“…This became possible with British Coal's computerized data base in the early 1990s. (British Coal ceased to exist in 1994 and the records, including seam analyses, were transferred to the National Geological Records Centre at the British Geological Survey) Using the data base in a collaborative study with industry, and backed up with additional analyses, the distribution of S in what were at that time key economic seams (including the Parkgate Seam) was investigated by Cavender [17] and reported in Cavender and Spears [18] and Spears et al [15]. It was found that the S contents of individual sections of the seam (plies) could be mapped and the distribution was not random as had been thought.…”
Section: Role Of Seawater On S and CL Concentrations In British Coalsmentioning
confidence: 99%